Liver Imaging Reporting and Data System (LI-RADS) v2018: differential diagnostic value of ADC values for benign and malignant nodules with moderate probability (LR-3) - Chen, Xue; Cai, Quanyu; Xia, Jinju; Huang, Huan; Li, Zhaoxing; Song, Kairong; Jia, Ningyang; Liu, Wanmin (Frontiers in Oncology, 2023)
To evaluate the usefulness of the apparent diffusion coefficient (ADC) in differentiating between benign and malignant LR-3 lesions classified by Liver Imaging Reporting and Data System 2018 (LI-RADS v2018).Retrospectively analyzed 88 patients with liver nodules confirmed by pathology and classified as LR-3 by LI-RADS. All patients underwent preoperative contrastenhanced MR examination, and the following patient-related imaging features were collected: tumor size, non-rim APHE nonrim APHE, non-peripheral washout nonperipheral "washout", enhancing capsule enhancing "capsule", mild-moderate T2 hypersignal mild-moderate T2 hyperintensity, fat in mass, restricted diffusion, and nodule-in-nodule appearance nodule-in-nodule architecture. We performed ROC analysis using SSPS 22.0 software and calculated the sensitivity and specificity.A total of 122 lesions were found in 88 patients, with 68 benign and 54 malignant lesions. The mean ADC value for malignant and benign lesions were 1.01 ± 0.15 × 10 3 mm 2 /s and 1.41 ± 0.31 × 10 3 mm 2 /s, respectively. The ADC value of malignant lesions was significantly lower than that of benign lesions, p < 0.0001. Compared with other imaging features, ADC values had the highest AUC (AUC = 0.909), with a sensitivity of 92.6% and a specificity of 74.1% for the differentiation of benign and malignant lesions.ADC values are useful for differentiating between benign and malignant liver nodules in LR-3 classification, it improves the sensitivity of LI-RADS in the diagnosis of HCC while maintaining high specificity, and we recommend including ADC values in the standard interpretation of LI-RADSv2018.